El control judicial de la regulación económica y el margen de deferencia en Estados Unidos: el fin del precedente Chevron - Hernández G, José Ignacio (Pontificia Universidad Católica del Perú, 2025)
In 2024, the United States Supreme Court overturned a landmark precedent, Chevron, which was initially adopted in 1984. Chevron had been the general doctrine used to define the scope of judicial review over regulatory agencies, based on deferential control over vague concepts established in statutes. However, in Loper Bright, the Court concluded that this deferential control was incompatible with judicial review. It is important to note that the Court did not challenge the constitutionality of the modern administrative state. The Supreme Court also acknowledged that courts should adopt a deferential review when a statute grants discretionary powers. Despite this, the Court ratified that agencies can only adopt regulations with vast economic and social impact upon express delegation of the statute. This could lead to the potential denial of any deferential review, advancing in the constitutional crisis of the modern administrative state due to the practical obstacles that impede Congress from exhausting vast regulations in statutes.

En 2024, la Corte Suprema de los Estados Unidos revocó un precedente histórico, Chevron, que fue adoptado inicialmente en 1984. Chevron había sido la doctrina general utilizada para definir el alcance de la revisión judicial sobre las agencias reguladoras, basada en el control deferente sobre conceptos vagos establecidos en los estatutos. Sin embargo, en Loper Bright, la Corte concluyó que este control deferente era incompatible con la revisión judicial. Es importante señalar que la Corte no cuestionó la constitucionalidad del estado administrativo moderno. La Corte Suprema también reconoció que los tribunales deben adoptar una revisión deferente cuando un estatuto otorga poderes discrecionales. A pesar de esto la Corte ratificó que las agencias solo pueden adoptar regulaciones con vasto impacto económico y social mediante delegación expresa del estatuto. Esto podría llevar a la potencial negación de cualquier revisión deferente, avanzando en la crisis constitucional del estado administrativo moderno debido a los obstáculos prácticos que impiden al Congreso agotar vastas regulaciones en los estatutos.
Juditial control of economic regulation and the margin of deference in the United States: the end of the Chevron precedent
Keywords: Judicial review; Regulatory agencies; Margin of deference; The Chevron doctrine; Revisión judicial; Agencias reguladoras; Margen de deferencia; Doctrina Chevron; https://purl.org/pe-repo/ocde/ford#5.05.00